Alternatives to custodial sentences: a Maqasidi approach - Boukerroucha, Halima (2014)
This paper aims to discuss the issue of alternatives to custodial sentences from a maqasidi approach. It assesses the consistency of this concept with the philosophy of Islamic criminal legislation and the viability of its application in light of the concept of crime and punishment in Islamic law. In doing so, the paper define custodial sentences in contemporary legislation. It then analyses the concept of imprisonment in the Quran and Sunnah and the practices of the companions. It also assesses the impact of the custodial sentences in modern practices with the aim to identify the conditions and parameters for the alternatives within the framework of maqasid al-Shariah in general and the maqasid of punishments in particular.